2018
DOI: 10.5430/jnep.v9n3p70
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous students: Barriers and success strategies-A review of existing literature

Abstract: There are many factors that effect the post-secondary completion rate of Indigenous students. The Indigenous student completion rate is a reflection of the number of students entering post-secondary education but is significantly affected by withdrawal rates (institutional withdrawals and student voluntary withdrawals). In the Saskatchewan Polytechnic School of Nursing, the Indigenous student withdrawal rate was 4.2% higher than the total nursing student population. Lower success rates among Indigenous student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Furthermore, Numerous studies (almost all Canadian and international articles) have suggested that Indigenous students' experience lower levels of high school graduation rates and/or academic preparedness in multiple subject areas for higher education (Nakata, 2004;Nelson, 2019;Preston, 2008). As such, lower graduation rates and/or inadequate academic preparation for higher education was described as a major or critical barrier of Indigenous students' academic attainment and success in higher education (Harper and Thompson, 2017;Stonechild, 2008).…”
Section: Indigenous Studentsmentioning
confidence: 99%
“…Furthermore, Numerous studies (almost all Canadian and international articles) have suggested that Indigenous students' experience lower levels of high school graduation rates and/or academic preparedness in multiple subject areas for higher education (Nakata, 2004;Nelson, 2019;Preston, 2008). As such, lower graduation rates and/or inadequate academic preparation for higher education was described as a major or critical barrier of Indigenous students' academic attainment and success in higher education (Harper and Thompson, 2017;Stonechild, 2008).…”
Section: Indigenous Studentsmentioning
confidence: 99%
“…In the United States, 36.2% of students from indigenous tribe entered college and completed studying in six years [25]. In Canada, less than 33.9% of indigenous people aged 25-64 achieve a post-secondary degree while non-indigenous reach 54% [26]. In Malaysia, native education has a high dropping out rate compared to other students, specifically in Terengganu, 83.4% of natives dropped out of school over the years [27].…”
Section: Literature Review 21 Education Attainment Of Indigenous Tribementioning
confidence: 99%